Analisis motivasi membaca novel di kalangan murid SMP pada Perpustakaan Umum Daerah Kabupaten Penajam Paser Utara - Rini Wedhayanti (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
This study aims to analyze the factors motivating Junior High School students in Penajam Paser Utara Regency to read novels, particularly those accessed through the Regional Public Library. Data on book borrowing in 2023 indicated that novels were the most popular collection, with female SMP students as the most frequent borrowers. This phenomenon warrants further investigation to understand the motivations behind this demographic's high interest in novel reading. This study employs a qualitative approach with data collection techniques through in-depth interviews and observations. Interviews were conducted with SMP students who actively borrow novels from the Regional Public Library, while observations were carried out to observe their interactions with the library collection and surrounding environment. The findings revealed that intrinsic motivations, such as the desire to explore new worlds, experience diverse emotions through stories, and escape momentarily from routines, are the primary drivers behind the interest in reading novels. Additionally, extrinsic factors like support and positive influence from family, friends, and teachers also significantly shape reading habits and interests. These findings highlight the crucial role of libraries in providing a collection of novels relevant to the interests and needs of teenagers, as well as creating a positive social environment that supports literacy activities. This study provides valuable insights for library management and educators in designing more effective and engaging literacy improvement strategies for SMP students. By understanding reading motivations, literacy programs, and activities can be designed to be more targeted and capable of fostering sustainable reading interest. Keywords: Reading Motivation, Reading Interest, Novels, Adolescents, Junior High School Students, Public Libraries